1988
DOI: 10.1159/000167576
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism and Hypotestosteronemia of Acute Renal Failure

Abstract: Acute and chronic renal failure are associated with a marked reduction in the serum levels of testosterone. The mechanisms underlying this abnormality are unknown. Certain data have implicated the high blood levels of parathyroid hormone (PTH) of uremia in the genesis of the hypotestosteronemia. The effects of 3 days of acute uremia in dogs with intact parathyroid glands and in thyroparathyroidectomized animals on serum testosterone levels and on the calcium content of the hypothalamus, pituitary gland, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous data from animal experiments 13 and studies of patients with secondary hyperparathyroidism as a result of renal disease 14,15 have indicated possible relationships between PTH excess, low circulating testosterone levels and sexual dysfunction. The association between bioavailable testosterone and primary parathyroid disease found in our study is, however, a new observation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from animal experiments 13 and studies of patients with secondary hyperparathyroidism as a result of renal disease 14,15 have indicated possible relationships between PTH excess, low circulating testosterone levels and sexual dysfunction. The association between bioavailable testosterone and primary parathyroid disease found in our study is, however, a new observation.…”
Section: Discussionmentioning
confidence: 99%
“…These include the heart [1-3], brain [4], liver [5], testes [6], pancreas [7,8], polymorphonuclear leukocytes [9][10][11], thymocytes [12], T [13] and B [14] cells. Also, the acute exposure of contain PTH receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition. Akmal et al [6] showed that hvpotestosteronaemia in acute renal fail ure in dogs is prevented by prior PTX. These authors sug gested that the effect of PTH excess on serum testosterone Effect of Parathyroidectomy on LH, Testosterone, and FSH might be mediated through the accumulation of calcium in hypothalamus, adenohypophysis, and testes.…”
Section: Discussionmentioning
confidence: 99%